THE ROLE OF PT. MEKAAR SYARIAH CIVIL NATIONAL CAPITAL FOR EMPOWERING WOMEN IN THE CITY OF LHOKSEUMAWE - Nofianti, Nofianti; Herlina, Herlina; Rahmi, Utia; Andriani, Rika; Sinta, Irada (RADJA PUBLIKA, 2022)
Today's women no longer only look after and care for family and household members, but also earn a living to help their husbands to fulfill all their daily needs and help improve their families by being housewives and also being career women. So, it is necessary to have a forum that can guide or empower women to face competition and make these women independent. With this, the government establishes a special agency for women who want to start or develop their business by providing capital and providing guidance and business development. This study aims to determine the role of PT. National Capital Madani Mekaar Syariah in Banda Sakti in empowering women. This research is a type of qualitative descriptive research and in collecting data using observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation and conclusion. The research results show that: PT. Mekaar Syariah National Madani Capital plays an important role in assisting the process of empowering women in terms of the programs implemented, namely providing capital and business assistance through forming groups as a means of carrying out empowerment for women who are their customers.